2004
DOI: 10.1002/chin.200426239
|View full text |Cite
|
Sign up to set email alerts
|

The Total Synthesis of Streptonigrin and Related Antitumor Antibiotic Natural Products.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The 5,8-quinolinedione derivatives were among the first compounds to be systematically modified in order to find products with higher biological activities, such as anticancer, anti-inflammatory or antibacterial [1][2][3][4][5][6][7][8][9]. For example, it was found that substitution of the electron-withdrawing groups at the 6-or 7-positions of the 5,8-quinolinedione led to an increase in the DNA degradation [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The 5,8-quinolinedione derivatives were among the first compounds to be systematically modified in order to find products with higher biological activities, such as anticancer, anti-inflammatory or antibacterial [1][2][3][4][5][6][7][8][9]. For example, it was found that substitution of the electron-withdrawing groups at the 6-or 7-positions of the 5,8-quinolinedione led to an increase in the DNA degradation [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nucleophilic attack takes place at the 2-and 4-positions. Quinolines and their derivatives are very important compounds because of their wide occurrence in natural products [1,2] and biologically active compounds [3][4][5][6][7][8]. These derivatives are also used for the preparation of nano-and meso structures having enhanced electronic and photonic properties [9,10] and are known to have applications as pharmaceuticals, agrochemicals and synthetic building blocks [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quinoline derivatives are known to possess diverse pharmacological properties such as antioxidant 18,19 , antibiotic 20,21 , cardiovascular 22 , anti-TB 23 , antiplatelet 24 , anticancer 25,26 , receptor antagonists 27 , NK3 receptor antagonists-II 28 , anti-inflammatory 29 , antimicrobial 30,31 , selective estrogen receptor modulators (SERMs) 32 and protein kinase inhibitor 33 . Keeping above in mind, we decided to synthesize conjugates of the above-mentioned moieties to study the biological profile of the resulting product.…”
Section: Introductionmentioning
confidence: 99%